Localized Corrosion: Passive Film Breakdown vs Pit Growth Stability: Part V. Validation of a New Framework for Pit Growth Stability Using One-Dimensional Artificial Pit Electrodes. Issue 11 (1st January 2019) - Li, Tianshu; Scully, J. R.; Frankel, G. S.
Abstract : Experimental evidence is provided to support the validity of a new framework for pit growth stability established in previous papers in this series. Downward potential scans from the diffusion-controlled condition were performed on SS316L one-dimensional (1D) artificial pit electrodes in 0.6 M NaCl. The variation of the critical pit surface potential for salt film formation with pit depth was in agreement with the theoretical prediction of the new framework. Using pits of different depths, the maximum pit dissolution current density, i diss, max, was obtained as a function of maximum pit surface potential, E max, at fixed pit surface metal cation concentrations, C surf, equal to the saturation concentration, C sat, and 70% C sat . The apparent Tafel slope of the pit dissolution kinetics determined using the downward potential scan of a 1D pit in the charge-transfer-controlled region, where C surf changes continuously during the scan, was smaller than the Tafel slope for i diss, max ( E max ) at a fixed C surf, indicating that C surf is a key parameter for pit dissolution. The critical concentration for pit stability/repassivation was found to be approximately 43% of C sat . Charge-transfer-controlled 1D pit growth was shown to be a transient state, which will spontaneously transition to diffusion-controlled growth in accordance with the predictions of the new framework.